Oxidation of alginate and pectate biopolymers by cerium(IV) in perchloric and sulfuric acid solutions: A comparative kinetic and mechanistic study. (15th March 2016) - Fawzy, Ahmed
Highlights: Oxidation of alginate and pectate biopolymers by Ce(IV) in acid solutions was studied. Oxidation rates in perchloric acid were higher than those observed in sulfuric acid. The main oxidation products were identified as mono-keto derivatives of biopolymers. Plausible mechanistic schemes have been proposed and the rate laws were derived. The constants associated with the reactions and activation parameters were evaluated. Abstract: The kinetics of oxidation of alginate (Alg) and pectate (Pec) carbohydrate biopolymers was studied by spectrophotometry in aqueous perchloric and sulfuric acid solutions at fixed ionic strengths and temperature. In both acids, the reactions showed a first order dependence on [Ce(IV)], whereas the orders with respect to biopolymer concentrations are less than unity. In perchloric acid, the reactions exhibited less than unit orders with respect to [H + ] whereas those proceeded in sulfuric acid showed negative fractional-first order dependences on [H + ]. The effect of ionic strength and dielectric constant was studied. Probable mechanistic schemes for oxidation reactions were proposed. In both acids, the final oxidation products were characterized as mono-keto derivatives of both biopolymers. The activation parameters with respect to the slow step of the mechanisms were computed and discussed. The rate laws were derived and the reaction constants involved in the different steps of the mechanisms were calculated.